2014
DOI: 10.1038/srep05899
|View full text |Cite
|
Sign up to set email alerts
|

The color red distorts time perception for men, but not for women

Abstract: We investigated the effect of the color red on time perception using a temporal bisection task with human adults. The results showed that the perceived duration of a red screen was longer than was that of a blue screen. However, the results reflected sex differences; men, but not women, overestimated the duration of the red screen. Additionally, the reaction times to a red screen were faster than those to a blue screen, and we found a significant correlation between reaction time and the tendency to overestima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 31 publications
(42 reference statements)
4
42
0
Order By: Relevance
“…The preference for red color could reduce the red color effect, particularly when women are exposed repeatedly to this favored color. This assumption is supported by a recent study showing that the repeated presentation of red distorts time perception in men but not in women (Shibasaki & Masataka, 2014), indicating "a sex difference in the emotional valence of red" (p. 3).…”
Section: Gender Differences In the Influence Of The Color Red On Perfmentioning
confidence: 55%
See 3 more Smart Citations
“…The preference for red color could reduce the red color effect, particularly when women are exposed repeatedly to this favored color. This assumption is supported by a recent study showing that the repeated presentation of red distorts time perception in men but not in women (Shibasaki & Masataka, 2014), indicating "a sex difference in the emotional valence of red" (p. 3).…”
Section: Gender Differences In the Influence Of The Color Red On Perfmentioning
confidence: 55%
“…Some of the previous studies found similar color effects for both genders (e.g., Maier et al, 2008;Mehta & Zhu, 2009), but others found a stronger effect of the color red on male than on female participants (Gnambs et al, 2010;Hill & Barton, 2005;Ioan et al, 2007;Shibasaki & Masataka, 2014). For example, Gnambs et al (2010) showed that men (but not women) scored significantly lower on a web-based general knowledge test when parts of the survey page were colored red as compared to green.…”
Section: Gender Differences In the Influence Of The Color Red On Perfmentioning
confidence: 77%
See 2 more Smart Citations
“…Whether or not this sex difference reflects different biases in social perceptions requires further investigation. For example, the colour red distorts time perception in men but not in women [19], and wearing red enhanced the probability of winning combat sport bouts in male, but not female, athletes [13,14]. Participants categorized targets significantly more often as 'angry' when presented in the red condition.…”
Section: Discussionmentioning
confidence: 95%